2006
DOI: 10.1152/advan.00052.2006
|View full text |Cite
|
Sign up to set email alerts
|

PGC-1α: a key regulator of energy metabolism

Abstract: Peroxisome proliferator-activated receptor-gamma coactivator (PGC)-1alpha is a member of a family of transcription coactivators that plays a central role in the regulation of cellular energy metabolism. It is strongly induced by cold exposure, linking this environmental stimulus to adaptive thermogenesis. PGC-1alpha stimulates mitochondrial biogenesis and promotes the remodeling of muscle tissue to a fiber-type composition that is metabolically more oxidative and less glycolytic in nature, and it participates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
814
0
12

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,078 publications
(852 citation statements)
references
References 74 publications
26
814
0
12
Order By: Relevance
“…HK‐II and PFK are the main rate‐controlling enzymes of glycolytic flux while PDH activity, which catalyzes the conversion of pyruvate to acetyl‐CoA, modulates mitochondrial glucose and fatty acid fluxes. Mitochondrial fatty acid (FA) β‐oxidation is a metabolic feature promoted by CR and exercise that is controlled by PGC‐1α, a member of a family of transcriptional coactivators, and the protein deacetylase SIRT3 (Hirschey et al., 2010; Liang & Ward, 2006). Western blot analysis showed significant accumulation of PGC‐1α and SIRT3 in muscle of RedTg mice compared to Wt controls (Figure 2c,d).…”
Section: Resultsmentioning
confidence: 99%
“…HK‐II and PFK are the main rate‐controlling enzymes of glycolytic flux while PDH activity, which catalyzes the conversion of pyruvate to acetyl‐CoA, modulates mitochondrial glucose and fatty acid fluxes. Mitochondrial fatty acid (FA) β‐oxidation is a metabolic feature promoted by CR and exercise that is controlled by PGC‐1α, a member of a family of transcriptional coactivators, and the protein deacetylase SIRT3 (Hirschey et al., 2010; Liang & Ward, 2006). Western blot analysis showed significant accumulation of PGC‐1α and SIRT3 in muscle of RedTg mice compared to Wt controls (Figure 2c,d).…”
Section: Resultsmentioning
confidence: 99%
“…PPARGC1A is a transcriptional co-activator that interacts with a broad range of transcription factors involved in a wide variety of biological processes, including glucose metabolism in the liver and muscle, mitochondrial biogenesis, lipid oxidation, and adipocyte differentiation. 22 One of the transcription factors regulated by PPARGC1A is PPARG. In line with the interaction effect of PPARGC1A with BMI in our study, Wei et al 7 found a significant interaction effect between two SNPs in the PPARG gene (rs4135304; rs4135247) and BMI on fasting plasma glucose levels in African Americans.…”
Section: Discussionmentioning
confidence: 99%
“…In liver, PPARGC1A down-regulation decreases gluconeogenesis, 22 which has a blood glucose lowering effect. In contrast, in vitro studies suggest that down-regulation of PPARGC1A in muscle increases insulin resistance by down-regulating GLUT4 transporters 22 and by stimulating muscle lipid accumulation. 33 This, in turn, increases blood glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…PGC1A and its target mitofusin-2 (MFN2) are both involved in mitochondrial biogenesis and in the maintenance of the mitochondrial network [6][7][8]. Moreover, MFN2 augments mitochondrial oxidative capacity for both glucose and lipids [9] and PGC1A increases expression of the insulinsensitive glucose transporter 4 [10].…”
Section: Introductionmentioning
confidence: 99%